ARUM KAHEMAN “INHALER AROMATERAPI PELANCAR ASI” INOVASI AROMATERAPI GALAKTAGOG YANG PRAKTIS DAN TERJANGKAU - Zahra Y A; Chairunnisa N; Nurahmatussa'diah S (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Background: Exclusive breastfeeding is the provision of breast milk without additional food or drink for six months. In Indonesia, coverage in 2024 was only 74.73%, still below the national target of 80% (BPS, 2024; Presidential Decree No. 72/2021). Stress has been shown to inhibit breast milk production by increasing cortisol, which suppresses prolactin and oxytocin (Matyas et al., 2024; Wambach & Spencer, 2024). Pharmacological approaches such as domperidone and metoclopramide are effective but carry the risk of arrhythmia and depression (Ou et al., 2021; Si et al., 2024; Hussain et al., 2021). Therefore, non-pharmacological interventions, including aromatherapy, are recommended. Fennel acts as a galactagogue (Triandini et al., 2022; Sari et al., 2023), while lavender and lemon have been shown to reduce anxiety and improve mood (Ropiah et al., 2023; Rahayu et al., 2023). Arum Kaheman, based on fennel-lavender and fennel-lemon, is designed to support successful lactation while also opening up natural product business opportunities for breastfeeding mothers in Indonesia. Methods: The study used a qualitative method, a pre-experimental design with a one-group pretest-posttest sampling approach of 40 respondents, and a questionnaire as the instrument. Results: The study showed that the increase in breast milk flow after using an aromatherapy inhaler fell within the moderate improvement criteria. It had an effectiveness or influence of 3.60% in increasing breast milk flow in breastfeeding mothers. Conclusion: The innovation of the aromatherapy inhaler has been proven to help improve breast milk flow in breastfeeding mothers and assist midwives in providing obstetric care to breastfeeding mothers